In vitro Anti-Cancer Activity of Plectranthus amboinicus (Lour.) Spreng. in DLA Cell lines - R, Jithesh Krishnan; Ramachandran, Asha; Sivadasan, Abhilash (Asian Journal of Biological and Life Sciences)
Background: Today, the number of cancer patients is increasing because of lifestyle, food habits, radiation, etc. Chemotherapy and other medicines cause many problems in the normal body. Discovering new cancer drugs from nature is crucial. Many available medicines are chemically manufactured, leading to numerous side effects. Therefore, the current emphasis has shifted towards exploring natural products, including plants and plant-derived substances, to pave the way for a potentially safer future in cancer treatment. Many of the naturally occurring products have many medicinal properties as well as anticancer activities. Many investigations were carried out to study the anticancer activities of different plant products, including leaf, bark, root, rhizomes, tubers, etc., in search of new drugs. Phytochemicals are the compounds that are present in plants; they have antimicrobial, antifungal, anti-inflammatory, and anticancer activities. A study on the “toxicity of phytochemicals against intestinal and nasopharyngeal bacteria” was conducted in our lab during 2016. Methanol and acetone extracts of six medicinal plants (Allium schoenoprasum, Cinnamomum zeylanicum, Plectranthus amboinicus, Ayapana triplinervis, Ocimum sanctum, and Piper nigrum) in different concentrations were tested for their antibacterial properties. It was revealed that the methanol extract of Plectranthus amboinicus shows high antibacterial properties. Aim: The present study mainly aimed at investigating the phytochemicals present in the methanol extract of P. amboinicus and its anti-cancer activities on DLA cell lines. Materials and Methods: The plant powder is employed for both organoleptic study and qualitative phytochemical analysis. Following standard procedures, it was dispatched to the Amala Cancer Research Centre for additional anticancer studies. Results: The phytochemical analysis revealed that the methanol extract of P. amboinicus is rich in bioactive compounds with flavonoids, glycosides, terpenoids, steroids, tannins, quinones, reducing sugar, anthocyanin, phenol, and flavanol. The plant showed 4.2, 12.6, and 30.4% cytotoxicity in DLA cell lines at concentrations of 50, 100, and 200 μg/ mL, respectively. There was no cell death in lower concentrations (10 μg, 20 μg). Conclusion: The results indicate that the plant exhibits a noteworthy variety of phytochemicals, and these compounds exert a direct impact on cancer cells at specific concentrations.
Keywords: Anticancer activity; DLA cell lines; Phytochemical; Plectranthus amboinicus